Determinação do momento crítico elástico à flambagem lateral com distorção de vigas mistas contínuas e semicontínuas - João Victor Fragoso Dias (2018)
Great attention has been given in the last years to steel and concrete composite beams due to the gains in strength and stiffness that can be obtained with the small cost of installing a shear connection between the steel profile and the concrete slab. In continuous and semicontinuous composite beams, close to the internaç supports, hogging bending moments are developed and the compressed bottom flange may buckle laterally in an instability known as lateral distortional buckling (LDB), characterized by a horizontal displacement and a twist of the bottom flange with distortion of the web. The calculation procedure in the Brazilian and European design standards is based on the reduction of the cross-section ultimate bending moment with a nondimensional parameter, which is calculated from the slenderness of the beam. This slenderness, in turn, needs a determination of the critical elastic moment to LDB. In literature, several formulations are proposed to determine this critical moment. Among them, some of the most relevant are presented by Roik et al. (1990) and Hanswille et al. (1998). equation has also been adopted by the Brazilian standard ABNT NBR 8800:2008. In the present work, a new procedure based on the elastic foundation beam theory is proposed to determine the critical moment of continuous and semicontinuous composite beams under uniform hogging moment. To assess the proposed procedure, 7,772 numerical models were developed in the general purpose finite element code ANSYS and the results were compared to the ones obtained with the new proposal. The procedure presented excellent agreement with the numerical results, with deviations that were below 10% in 97.29% of the models and average deviation of 2.33%. The formulations of Roik et al. (1990) and by Hanswille et al. (1998) did not lead to such satisfactory results, presenting average deviations of 12.41% and 16.51% respectively.